Acknowledgement to reviewers - Editor-in-Chief (Journal of Interdisciplinary Sciences)
The Journal of Interdisciplinary Sciences (JIS) wishes to thank all the reviewers for their intellectual contributions by timely reviewing manuscripts, and supporting the journal’s vision of “Enriching Beautiful Minds towards Intelligent Minds”. From the desk of the Editor-in-Chief, the Journal of Interdisciplinary Sciences (JIS) would like to thank all the reviewers who made it possible to publish this volume, Volume 3, Issue 1, May 2019. Let us join and collaborate together to ENRICH the BEAUTIFUL MINDS TOWARDS INTELLIGENT MINDS Mani Man Singh Rajbhandari Katarina Kostelić Alan Schoenfeld Ekaterina Khitruk Heleen Pott Gloria Erima Raf Meesen Apostolos P Georgopoulos John W. Gaddy Per Ahlberg Emily Sitienei Tuncay Colak Olutola Oluwole Niyazi ACER Ubiratan D’Ambrosio S. Deniz Gokcora Richard J. Herdlein Rebecca Freeth Peter Liljedahl Servet Celik Carol A. Fowler